Sosialisasi NIB dan SP-PIRT terhadap UMKM Kelurahan Sukorame yang Dilakukan oleh Mahasiswa PKKM Bina Desa UPN Veteran Jawa Timur - Anugrah, Vikri Jaya; Prabowo, Budi; Hidayat N, Rusdi; Dwiridhotjahjono, Jojok (Jurnal Bisnis Indonesia, 2024)
Sukorame sub-district has great potential for SMEs, so this is our focus in carrying out communityservice activities in Sukorame Gresik sub-district. This research aims to help MSMEs to develop theirbusiness in terms of managing the legality of their business including HALAL AND SP-PIRT. InIndonesia, it is mandatory for all MSMEs to have legality in their business, which includes halal nib,and also pirt to make MSME businesses in Indonesia more developed and able to advance to an evenbigger Rana. With this activity of making halal and pirt certification, it is intended to help MSMEs inthe Sukorame sub-district so that they can grow bigger and can be distributed to regions in Indonesiawith legality that has been determined and is mandatory for all MSMEs in Indonesia. This lack ofunderstanding by MSMEs in the Sukorame Gresik sub-district is what made us create a communityservice work program related to business legality, one of which is creating a halal and pirtsocialization work program. Because with halal certification, the public or consumers can easilyknow that the products they consume are guaranteed to be halal. Likewise, pirt is a factor in thedevelopment of MSMEs in Indonesia, because it is so important for MSMEs today, as well asguaranteeing and also as proof that the food and beverage business produced and sold by this homeindustry meets applicable food product standards.Keywords: Socialization; MSMEs; HALAL; SP-PIRT